2019
DOI: 10.1021/acsenergylett.9b00912
|View full text |Cite
|
Sign up to set email alerts
|

High-Output and Bending-Tolerant Triboelectric Nanogenerator Based on an Interlocked Array of Surface-Functionalized Indium Tin Oxide Nanohelixes

Abstract: We present a high-performance flexible triboelectric nanogenerator (TENG) based on an interlocked array of surface-functionalized indium tin oxide (ITO) nanohelix (NH) structures. The structural properties of ITO NHs, including a high nanoscale roughness and unique spring-like geometry, provide a large surface area for an effective friction, enhanced tolerance to bending strain, and operational reliability. The TENG device with surface-functionalized ITO NHs exhibits a significantly enhanced (over 340 times) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…The proposed mask comprises of three layers -the first two layers (inner and middle) are made up of two materials from the two extreme ends of a triboelectric series, which will enhance the chances of getting more static electricity due to friction between these two layers. The extreme outer part of the mask is designed to develop the produced electrostatic energy (possible to produce in the range of mW to kW [2][3][4][5][6]) by forming an electrically active mesh that might have the capability to destroy the activity of the incoming virus. The conceptualized self-chaged mask can be functioned from the both sides.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…The proposed mask comprises of three layers -the first two layers (inner and middle) are made up of two materials from the two extreme ends of a triboelectric series, which will enhance the chances of getting more static electricity due to friction between these two layers. The extreme outer part of the mask is designed to develop the produced electrostatic energy (possible to produce in the range of mW to kW [2][3][4][5][6]) by forming an electrically active mesh that might have the capability to destroy the activity of the incoming virus. The conceptualized self-chaged mask can be functioned from the both sides.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…[213,214] Chun et al reported that electronegative and electropositive plates could be prepared using the same poly(ethylene terephthalate) (PET) coated with ITO nanohelix (NH) structures (i.e., ITO NHs). [215] In detail, when the ITO NHs were coated by amino group-functionalized polymers (i.e., poly-l-lysine), they exhibited a tribopositive property with a hydrophilic surface (a water contact angle of ≈58°). In contrast, when the outermost surface of the ITO NHs was coated by a fluorine-functionalized molecule (4,5-difluoro-2,2-bis(trifluoromethyl)-1,3-dioxole), the surface displayed a tribonegative property with a hydrophobic surface (a water contact angle of ≈151°) (Figure 6e).…”
Section: Interfacial Design For Flexible Tengsmentioning
confidence: 99%
“…e,f) Adapted with permission. [215] Copyright 2019, American Chemical Society. [216] Copyright 2020, American Chemical Society.…”
Section: Interfacial Design For Flexible Tengsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another patterning method is adopting the etching through a mask and growing material in a patterned template. [34][35][36][37][38][39] These patterning methods also require an additional complicated process because an additional etching process is required for pattern formation on an already prepared membrane. Photolithography cannot be used for the PVDF material, because the etching process is difficult for these organic materials.…”
Section: Introductionmentioning
confidence: 99%